ANALISIS KORELASI PROJECT-BASED LEARNING (PJBL) DENGAN PENDIDIKAN KARAKTER: STUDI BIBLIOMETRIK DENGAN APLIKASI VOSVIEWER - Thomana, Charles (Sekolah Tinggi Kateketik dan Pastoral Rantepao (STIKPAR) Toraja, 2024)
Project-Based Learning (PjBL) is one of the innovative learning models that teachers can use to improve students' character. The purpose of this research is to see the relationship between Project-Based Learning and character education through bibliometric analysis which is the result of the Publish or Perish 8 application dataset by referring to articles in Google Scholar which are then converted with VosViewer. The results of the bibliometric analysis show that Project-Based Learning is closely related to character education. In this analysis, the researcher then presents several research results in the form of articles that show how Project-Based Learning impacts the development of learners. In the end, the author also found that further research that can be done based on the bibliometric analysis is by linking character education and Project-Based Learning with local wisdom owned by each educational institution.